2013
DOI: 10.1017/s1047951113000309
|View full text |Cite
|
Sign up to set email alerts
|

22q11.2 deletion syndrome as a risk factor for aortic root dilation in tetralogy of Fallot

Abstract: Children with tetralogy of Fallot with 22q11.2 deletion and aortic arch anomalies have increased aortic annular and aortic sinus dilation. Further longitudinal study is needed to assess whether both features are associated with progressive aortic root dilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 27 publications
(50 reference statements)
1
15
1
Order By: Relevance
“…Although the majority of patients with Turner syndrome in the present study had BAV, this chromosomal anomaly has been identified previously as an independent risk factor for AoD [12]. The second most common chromosomal abnormality identified was 22q11.2 deletion syndrome, a condition that also appears to be an independent risk factor for AoD regardless of the presence of conotruncal defects [8,9]. Structurally normal hearts, ASD/VSDs, and subaortic stenosis were frequent in the remaining cases suggesting that, in some instances and depending on the associated physical exam findings or medical history, primary chromosomal abnormalities should be ruled out prior to defining a case as being of "idiopathic" origin.…”
Section: Discussionsupporting
confidence: 47%
“…Although the majority of patients with Turner syndrome in the present study had BAV, this chromosomal anomaly has been identified previously as an independent risk factor for AoD [12]. The second most common chromosomal abnormality identified was 22q11.2 deletion syndrome, a condition that also appears to be an independent risk factor for AoD regardless of the presence of conotruncal defects [8,9]. Structurally normal hearts, ASD/VSDs, and subaortic stenosis were frequent in the remaining cases suggesting that, in some instances and depending on the associated physical exam findings or medical history, primary chromosomal abnormalities should be ruled out prior to defining a case as being of "idiopathic" origin.…”
Section: Discussionsupporting
confidence: 47%
“…In this population some of the diagnoses included major aneuploidies that should be easily [6][7][8][18][19][20][21][22][23][24][25] In many cases, in spite of lacking further supporting clinical evidence of a direct link between AoD and the genes involved in the remaining patients with cytogenetic abnormalities, other potential candidate genes with relationships to cardiac morphogenesis or pathology were identified ( Table 3). [26][27][28][29][30][31][32][33][34][35] We also were able to identify other less common genetic conditions in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Chromosomal syndromes such as Turner syndrome and 22q11.2 deletion syndrome have been independently identified to be risk factors for AoD, apart from the presence of bicuspid aortic valve (BAV) or other CHDs known to be associated with de novo or postsurgical AoD and aortic dissection (i.e., conotruncal defects or ventricular septal defects). [6][7][8] Patients with Noonan syndrome seem to be at a higher risk for annular AoD and aortic root aneurysms, whereas cases of thoracic aortic dissection have been reported in association with autosomal dominant polycystic kidney disease. 5,9 Sinus of Valsalva aneurysms have also been described in patients with Klippel-Feil syndrome, cutis laxa, and Treacher-Collins syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…c o m / l o c a t e / i j c a r d common problems in patients with TOF [1]. It is frequent in patients with right aortic arch, pulmonary atresia and a history of an aorto-pulmonary shunting, and some patient's demographics, such as male sex and the association of chromosome 22q11.2 deletion [4,5]. Our patient has several risk factors for aortopathy, that is, male sex, right aortic arch and pulmonary atresia.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%